OPTIMIZING RICE HUSK ASH FOR USE AS A POZZOLANIC CEMENT REPLACEMENT MATERIAL - Suhail Zaffar; Aneel Kumar; Abdullah Saand; Naeem Aziz (Spectrum of Engineering Sciences, 2025)
This study was conducted to determine the optimal conditions for producing pozzolanic ashes from Rice husk for use as cement substitute materials. When the Rice husk turned into ash, it develops a pozzolanic character due to the presence of silica. However, the transformation of silica from amorphous to crystalline and its associated pozzolanic reactivity depends on the calcination temperature, duration, and grinding. In this research the Rice husk swere calcined at three different calcination temperatures (300oC, 400oC, and 800oC) for 2-, 4-,6- and 8-hours duration. The obtained ashes were ground for 30 minutes and replaced by 20% with cement. The samples containing ashes were tested for compressive strength, X-ray diffractometry (XRD), weight loss, and strength activity index (SAI). It was observed that the RHA calcinated at 600oC for 2 hours showed better strength. The materials ground for the higher duration is recommended for higher SAI.